(untitled) (Itinera, 2021)
In the movie Babette’s Feast a gastronomic poem transforms the inflexibility of political power into beautiful flavor. A popular Korean idiom hit like crashing Buk-Eu (« dried cod » in Korean) represents the catharsis against the injustice over the women from the machismo society, by a violent gesture at the moment of cooking. Touching the flesh gives an ambivalence of sensing between the horror of necrophagous human and the gustatory pleasure of eating the prey. As Gilles Deleuze says, the meat is the zone of indistinction and indetermination between the human being and the animal. This morbid and culinary touch finally converts our fear into the pleasure of flavor at the moment of tasting. After his Histoire de l’œil, Georges Bataille published an article in the journal Document (n°4, September 1929) written about the eye as a means of expressing « cannibal sweetmeat » (an expression defined by Stevenson) where the ambivalent sense represents the fascination and the horror. The visual activity is limited to the jealousy, to the fierceness of unilateral seduction and excessively to the voyeurism. Our eye is an affective instance, which makes the desire and the horror meet each other.